2016
DOI: 10.7324/japs.2016.60304
|View full text |Cite
|
Sign up to set email alerts
|

Repeated toxicological study and cardiotoxicity of hydroalcoholic root extract of Paullinia pinnata L (Sapindaceae).

Abstract: Paullinia pinnata L. is a plant widely used in African traditional medicine especially in the treatment of erectile dysfunction. This study aims to evaluate the cardiotoxicity of 50% hydroalcoholic extract of the roots of P. pinnata. The result of the acute toxicity test has shown a LD50 greater than 5000 mg/kg. During the 28 days subchronic administration, P. pinnata has increased significantly the relative weight of kidney. P. pinnata has induced also a microcytosis and an isolated hypochromia. Renal injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…This result is in accordance with a previous work that showed renal injuries by the increase in blood urea, creatinine, potassium, and chlorine. 27 However it is not in agreement with a previous finding that revealed that P pinnata aqueous ethanol roots showed no significant increase in biochemical parameters of the extract-treated animals at the doses of 375, 750, and 850 mg/kg. 13 Relative organ weight was determined to ascertain an eventual toxic effect of the extract on the liver and kidney.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This result is in accordance with a previous work that showed renal injuries by the increase in blood urea, creatinine, potassium, and chlorine. 27 However it is not in agreement with a previous finding that revealed that P pinnata aqueous ethanol roots showed no significant increase in biochemical parameters of the extract-treated animals at the doses of 375, 750, and 850 mg/kg. 13 Relative organ weight was determined to ascertain an eventual toxic effect of the extract on the liver and kidney.…”
Section: Discussioncontrasting
confidence: 93%
“…25 The acute and subacute toxicity of the methanolic extract of the leaves of P pinnata was reported as well as the repeated toxicological study and cardiotoxicity of hydroalcoholic root extract. 26,27 Phytochemical studies of P pinnata have demonstrated the presence of phenols, alkaloids, flavonoid, sterols, tannins, and other classes of secondary metabolites. 18,28,29 Despite the fact that P pinnata has been intensively screened for pharmacological activities, few studies revealed its properties on infectious diarrhea.…”
mentioning
confidence: 99%
“…Medicinal plants could increase blood flow to sex organs via the increase of the biological activity of nitric oxide synthase or which enhances the stimulation of LH by acting on the anterior pituitary gland example of such agents is Allicin and Rg1 found in Allium sativum and ginseng respectively 47,91,122 . Aphrodisiac medicinal plants could also act by the release of minerals and vitamins that are needed for optimal reproductive functions [47,75,89,90] . Free radicals are the inevitable by-products of biological redox reactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is a woody creeper or climber with rigid stems. The leaves are pinnate with five leaflets, the terminal leaflet being the largest as shown in Figure 36.0 [47,84,90] . Elemental analysis of the root revealed the presence of four elements: calcium, magnesium, potassium and zinc which were significantly high.…”
Section: Anthocleista Djalonensis a Chev Loganiaceous Fig 340: Photograph Of Anthocleista Djalonensismentioning
confidence: 99%
“…D. multiflora and P. pinnata are used to treat diarrhea and other infectious diseases. To date, few studies revealed pharmacological properties of D. multiflora while many of them focussed on biological properties of P. pinnata [42][43][44] . However, no previous study was carried out to understand their mechanism of action in order to clarify their biological activity.…”
Section: Discussionmentioning
confidence: 99%